O liberalismo e as proposições de John Dewey para a educação elementar - Medeiros, Verenice Mioranza de (2013)
Our purpose with this research is the analysis of liberalism in its historical process of re-articulation. We do this analysis from the study of the theoretical propositions John Dewey for elementary education that here understood like that designed to teach the rudiments minimum for workers, as would say Adam Smith in the eighteenth century. This study is justified by the need who we feel to deepen the theoretical basis to enable us to analyze the social and educational policies implemented by liberal states. We believe that the study of Dewey enables us to understand the implications of liberalism for the educational field. In the introduction we present our object, the organization of the study and considerations regarding the design of the State and social policies that guide our analysis. In the section entitled “The liberal thinking in its different phases," we describe some of the phases of the liberalism and its processes of crisis and re-articulation with the capitalist system. In the third chapter, we situate Dewey and the progressive school movement in the social, political and economic development of the United States. In the section "John Dewey and the propositions for elementary education: relations with the liberalism", we situate Dewey's thought as a classic in dialogue with the social, political and economic questions of their time and we present reflections on his proposals for the elementary education. In closing remarks, we recovered some questions that were presented throughout the text and we highlight our understanding that John Dewey, like the other liberals of his time, feared to lose the command to the socialist or fascist groups in ascendancy in the period. In this direction, the output proposed by Keynes, in the second phase of liberalism, joined it to the educational model proposed by Dewey, resulting in a broad ideological reform that got full support of the capitalists, which reaches until today.